Analysis of 15 STR loci in Chinese population from Sichuan in West China - Zhang, Haijun; Li, Yingbi; Jiang, Jiping; Zhang, Ji; Wu, Jing; Du, Hong; Yan, Jing; Shen, Yuehua; Hou, Yiping (Forensic science international, 2007)
Allele frequencies for 15 STR loci found in PowerPlex 16 System kit were determined in a sample of 200 unrelated individuals living in Sichuan area in west China. The values of observed heterozygosity (Ho), power of discrimination (PD), probability of paternity exclusion (PE) and polymorphism information content (PIC) were calculated. All loci were in accordance with Hardy–Weinberg equilibrium ( p < 0.05). The obtained frequency distributions were compared with other previously reported population data.